Presença de micro-organismos multirresistentes antes e após desinfecção em ambiente hospitalar - Pitta, Fernanda Donadio (2011)
Hospital infections and the resistance of microorganisms are a major problem and a challenge to health services and health professionals, who have sought effective measures to prevent and control these infections. The hospital environment is strongly associated with nosocomial infections, providing contact with and transmission of microorganisms. We performed a quantitative and qualitative research in an Inpatient Unit of the University Hospital of Londrina, which aimed to evaluate the presence of microorganisms multiresistant (MR) to antimicrobials before and after terminal disinfection of the environment, using a microbiological analysis of material collected from June 2010 to May 2011. We performed 256 cultures, collected with a swab, before and after terminal disinfection of the beds, benches, bells and serum support, involved with patients with more than 48 hours of hospitalization. The microorganisms studied were: methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus sp (VRE), Enterobacteria producing ESBL (extended spectrum beta lactamase), Enterobacteria producing carbapenemases and metalobetalactamase; and non-fermenting bacilli resistant to carbapenem. Of the samples, 89.8% (230) of cultures were negative and 10.2% (26) positive. Before disinfection, 85% (109) of cultures were negative and 15% (nineteen) positive, and after disinfection the number of negative cultures increased to 95% (121) and the number of positive decreased to 5% (seven). Of the 26 positive cultures, nineteen were before and seven after disinfection, with 39% (ten) in the beds, 31% (eight) in the benches, 15% (four) in the bells and 15% (four) in serum supports. There was a prevalence of vancomycin-resistant Enterococcus (31%) and Acinetobacter baumanii (27%). Statistical analysis was performed using the chi-square and Fischer's Exact test, considering 95% of confidence. Positive cultures of the beds were statistically significant, and a culture showed the Klebsiella pneumoniae (KPC) bacterium prior to disinfection, continuing in bed even after disinfection. In the benches, two bacteria that were present before disinfection remained after disinfection, Acinetobacter baumanii and Klebsiella pneumoniae, and two sites that did not have any bacteria before disinfection showed MRSA and VRE after disinfection. In a culture of the bells and serum supports, bacteria also remained present in the sites even after disinfection, A. baumanii and MRSA, respectively. The average hospital stay patients was of nine days, and of all positive cultures of the environment, 62% were from patients with up to seven days, and 38% of patients with more than seven days after admission.